Existence and exponential stability of periodic solution for fuzzy BAM neural networks with periodic coefficient - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We obtain conditions for the existence of solutions of nonlinear differential equations in the space of functions bounded on the axis by using a local linear approximation of these equations.